The value of using short-format podcasts to enhance learning and teaching - Catherine Sutton-Brady; Karen M. Scott; Lucy Taylor; Giuseppe Carabetta; Steve Clark (Association for Learning Technology, 2009)
This paper presents the findings of a podcasting trial held in 2007–2008 within the Faculty of Economics and Business at the University of Sydney, Australia. The trial investigates the value of using short-format podcasts to support assessment for postgraduate and undergraduate students. A multi-method approach is taken in investigating perceptions of the benefits of podcasting, incorporating surveys, focus groups and interviews. The results show that a majority of students believe they gained learning benefits from the podcasts and appreciated the flexibility of the medium to support their learning, and the lecturers felt the innovation helped diversify their pedagogical approach and support a diverse student population. Three primary conclusions are presented: (1) most students reject the mobile potential of podcasting in favour of their traditional study space at home; (2) what students and lecturers value about this podcasting design overlap; (3) the assessment-focussed, short-format podcast design may be considered a successful podcasting model. The paper finishes by identifying areas for future research on the effective use of podcasting in learning and teaching.